People's Republic of China poverty reduction and regional cooperation fund annual report 2020 (Annual reports of the PRC regional cooperation and poverty reduction fund)
This report provides information about the technical assistance and grants provided through the People’s Republic of China Poverty Reduction and Regional Cooperation Fund (PRC Fund) in 2020.